EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN METODE SNOWBALL DRILLING TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR - Eka Fitria Ningsih; Mardiyana Mardiyana; Gatut Iswahyudi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of this research was to investigate the effect of learning models on learning achievement viewed from self regulated learning. The learning models compared were cooperative learning model of the TAI type with the snowball drilling method, model of the TAI and the direct learning model. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VII of State Junior Secondary Schools of North Lampung regency. The samples of the research were taken by using the stratified cluster random sampling technique. They consisted of 326 students from State Junior Secondary School 1 of South Abung, State Junior Secondary School 2 of South Abung, and State Junior Secondary School 2 of Abung Semuli. The samples were divided into three classes, namely: 109 in Experimental Class 1, 107 in Experimental Class 2, and 110 in Control Class. The instruments to gather the data of the research were test of learning achievement in Mathematics and questionnaire of self regulated learning. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The conclutions of this research were as follows. (1) The cooperative learning model of the TAI type with the snowball drilling method resulted in a better learning achievement in Mathematics than TAI type and the direct learning model, and the cooperative learning model of the TAI type resulted in a better learning achievement in Mathematics than the direct learning model. (2) The students with the high self regulated learning had a better learning achievement in Mathematics than those with the moderate and low self regulated learning categories, and the students with the moderate self regulated learning had a better learning achievement in Mathematics than those with the low self regulated learning. (3) There was an interaction among learning models and the categories of self regulated learning on learning achievement in Mathematics.Keywords : TAI, snowball drilling, self regulated learning.